Hukum dan Kearifan Lokal Dalam Bisnis Pariwisata di Indonesia - Ade Saptomo; I Nyoman Putu Budiartha; Lulus Purna Malintang (Kertha Wicaksana, 2026)
Indonesia is a diverse archipelago, large and small; each archipelago boasts diverse cultures and natural resources, including volcanoes, verdant mountains, beautiful oceans, and beaches. The island of Bali is no different. It boasts not only the beauty of its landscapes but also the creative talents of its inhabitants, making their ideas, hard work, and handicrafts attractive to showcase and even sell as separate assets, skills not possessed by islanders in other countries. The question is how and how to market these natural resources and skills in the tourism business. To answer this question, this paper introduces the concept of local wisdom in the tourism business in Indonesia, specifically Bali, which has long been known as the Island of the Gods. This concept, in addition to legal policies that support tourism, also relies on local strengths, namely the backcountry and the frontcountry, one party and the other, to develop local cultural behavior as a wealth of local wisdom in the tourism business.